A Prospective Outcome Assessment After Bronchoscopic Interventions for Malignant Central Airway Obstruction. Issue 2 (April 2020) - Mohan, Anant; Shrestha, Prajowl; Madan, Karan; Hadda, Vijay; Pandey, Ravindra M.; Upadhyay, Ashish; Khilnani, Gopi C.; Guleria, Randeep
Abstract : Background: A systematic assessment of comprehensive clinical outcomes after various therapeutic procedures for malignant central airway obstruction (CAO) is lacking. Methods: Patients with symptomatic malignant CAO undergoing various therapeutic bronchoscopy procedures were assessed for symptomatic and functional improvement using the Speiser Score, spirometry, 6-minute walk distance (6MWD), and St. George Respiratory Questionnaire (SGRQ) up to 3 months after the procedures. Results: A total of 83 intervention procedures were performed in 65 patients, comprising 43 (66.2%) male individuals [overall mean age, 52.4; SD, 15.4 y]. The majority of these (92.3%) was done using rigid bronchoscope under general anesthesia. Airway stenting was the most common intervention performed (56.6%), followed by mechanical debulking (26.5%), cryodebulking (6%), electrosurgical removal (4.8%), balloon dilatation (3.6%), and laser ablation (2.4%). A total of 15 complications (18.1%) were noted. Of these, 8 (53.3%) were early complications and 7 (46.7%) were late complications. Early complications included airway bleeding, hypoxia, vocal cord injury, laryngeal injury, and pneumothorax. Late complications included significant granulation tissue formation in metallic stents and lung collapse because of mucus plug. The survival rates at 4, 8, and 12 weeks were 83%, 70.7%, and 66.1%, respectively. Significant improvement was observed in dyspnea, cough, Speiser Score, 6MWD, forced expiratory volume in 1 s, forced vital capacity, and SGRQ scores at 48 hours, 4 weeks, and at 12 weeks after the procedures and no procedure-related mortality occurred. Conclusion: Various therapeutic bronchoscopic interventions, including combined modalities, provide rapid and sustained improvements in symptoms, respiratory status, exercise capacity, and quality of life in malignant CAO and have a good safety profile. Abstract : Supplemental Digital Content is available in the text.